Aplicabilidade De Uma Escala Qualitativa De Sondagem Do Desenvolvimento Acadêmico E Neuropsicomotor Para Alunos Nos Três Primeiros Anos Do Ensino Fundamental Na Percepção Do Professor - Juliao, Bruna De Oliveira [UNIFESP] (2017)
The Evaluation Of Learning, With Emphasis On Monitoring The Progressive Acquisition Of Reading, Writing And Mathematical Skills, As Well As The Development Of Neuropsychomotor Skills, Can Be A Process Of Extreme Importance In The Detection Of Children At Risk For Learning Problems, As Well As In The Identification Of Individual Needs That Subsidize Appropriate Educational Interventions That Promote A Satisfactory Learning. However, In Brazil, There Are Still Few Instruments, Destined For Teachers In A Classroom Context, That Specifically Consider Neuropsychomotor Milestones Of Students In Elementary Grades. Thus, The Development Of Instruments That Help Teachers In Their Pedagogical Practice, By Guiding And Monitoring The Progress Of Pupils' Academic And Neuropsychomotor Development Throughout The School Year Is Necessary. This Study Aimed To Analyze How Teachers Evaluated The Adequacy And Applicability Of A Qualitative Scale Of Academic And Neuropsychomotor Development For Students In The First Three Years O